The Effect of Recitation Method on Learning Outcomes of â€œLife Eventsâ€ of 5th Grade - Ilyas Habibulloh, Muhammad; Nuruddin, Muhammad (IJPSE : Indonesian Journal of Primary Science Education, 2021)
This study aims as a way to determine the effect of the recitation method on learning outcomes of events in life that focuses on sub-theme 2 national events about the proclamation of independence day at SDN Gongseng 1 Jombang. As we know that the average learning process in schools is still centered on the teacher himself. By using the right application, it is certain that it will have a good impact on the quality of education. The lack of student interest in the methods taught by the teacher had a significant impact. In the process of working on questions, for example, students are less able to understand what is conveyed by the teacher who is able to provide a learning process whose substance is carried out by selecting the appropriate method. This research is pre-experimental research design, in the form of one-group pretest-posttest. The sample of this study consisted of 9 boys and 10 girls totaling 19 students who were in the experimental class. In the academic year 2021, it can be seen that the results of the pretest and posttest data of students by using the recitation method have sig. 0.000 < 0.05. From these results, it can be concluded that the effect of recitation has an influence on classroom learning by using conventional methods.